2D/1D Bi12O17Cl2/β-Bi2O3 heterojunction photocatalysts with boosted photocatalytic performance. Issue 30 (8th July 2021) - Wang, Bo; Qian, Hao-Zhi; Peng, Yin
Abstract : A novel 2D/1D Bi12 O17 Cl2 /β-Bi2 O3 heterostructure displays excellent photocatalytic degradation of methyl orange and phenol under solar light irradiation. The enhanced photocatalytic activity is ascribed to the unique vertical 2D Bi12 O17 Cl2 nanosheets. Abstract : Novel 2D/1D Bi12 O17 Cl2 /β-Bi2 O3 heterostructures were synthesized by calcining Bi(OHC2 O4 )·2H2 O/BiOCl precursors. Bi12 O17 Cl2 nanosheets grow vertically on the β-Bi2 O3 rods by crystallographically oriented epitaxial nucleation and growth, which increases the interface quality and then provides the smallest penetration barrier for electron–hole pair transfer at interfaces. The photocatalytic results show that Bi12 O17 Cl2 /β-Bi2 O3 displays higher photocatalytic activity than β-Bi2 O3 porous rods and Bi12 O17 Cl2 nanosheets for degrading methyl orange (MO) and phenol under solar light irradiation. This outstanding photocatalytic activity is ascribed to the formation of a 2D/1D Bi12 O17 Cl2 /β-Bi2 O3 heterostructure. This unique configuration results in the exposure of almost the entire surface of the 2D Bi12 O17 Cl2 nanosheets and increases the charge separation and transfer rate. Radical scavenger experiments prove that the photogenerated holes and ˙O2 − play key roles in the photodegradation process.